Boosting Pseudocapacitive Behavior of Supercapattery Electrodes by Incorporating a Schottky Junction for Ultrahigh Energy Density - Seenivasan, Selvaraj; Shim, Kyu In; Lim, Chaesung; Kavinkumar, Thangavel; Sivagurunathan, Amarnath T.; Han, Jeong Woo; Kim, Do‑Heyoung (Nano-Micro Letters, 2023)
Pseudo-capacitive negative electrodes remain a major bottleneck in the development of supercapacitor devices with high energy density because the electric double-layer capacitance of the negative electrodes does not match the pseudocapacitance of the corresponding positive electrodes. In the present study, a strategically improved Ni-Co-Mo sulfide is demonstrated to be a promising candidate for high energy density supercapattery devices due to its sustained pseudocapacitive charge storage mechanism. The pseudocapacitive behavior is enhanced when operating under a high current through the addition of a classical Schottky junction next to the electrode–electrolyte interface using atomic layer deposition. The Schottky junction accelerates and decelerates the diffusion of OH‒/K+ ions during the charging and discharging processes, respectively, to improve the pseudocapacitive behavior. The resulting pseudocapacitive negative electrodes exhibits a specific capacity of 2,114 C g−1 at 2 A g−1 matches almost that of the positive electrode’s 2,795 C g−1 at 3 A g−1. As a result, with the equivalent contribution from the positive and negative electrodes, an energy density of 236.1 Wh kg−1 is achieved at a power density of 921.9 W kg−1 with a total active mass of 15 mg cm−2. This strategy demonstrates the possibility of producing supercapacitors that adapt well to the supercapattery zone of a Ragone plot and that are equal to batteries in terms of energy density, thus, offering a route for further advances in electrochemical energy storage and conversion processes. Highlights: 1 Incorporation of Schottky Junction increases the pseudocapacitive mechanism at higher current rate. 2 The pseudocapacitance behavior of the positive and negative electrodes is balanced to construct a solid-state supercapattery device. 3 An energy density of 236.14 Wh kg−1 is achieved for solid-state supercapattery device.